So you would do 13+2 then add 3 then plus that by five
Answer:22
Step-by-step explanation:3(5-1)+2(5)
3×4 +10
12+10=22
A)
Vf² = vi² + 2ad Subtract 2ad from both sides
Vf² - 2ad = vi² Find the square roots of both sides
√(Vf² - 2ad) = √(vi²) Cancel out the squares with the square roots
Vf - √(2ad) = vi Switch the sides to make it easier to read
vi = Vf - √(2ad)
B) Vf² = vi² + 2ad Subtract vi² from both sides
Vf² - vi² = 2ad Divide both sides by 2a
(Vf² - vi²) / 2a = d Switch the sdies to make it easier to read
d = (Vf² - vi²) / 2a
we need to get a common denominator
2/3 2/3 * 5/5 = 10/15
6 2/3 = 6 10/15 < 6 12/15
so 6 2/3 < 6 12 /15
Set up a proportional relationship:
xf/1n=(f/5)/(n/3)
xf/1n=3f/(5n) multiply both sides by 1n
xf=3f/5 so
x=3/5
Dave must mix in 3/5 of a cup of fruit with a single cup of nuts.
You could of also just noted that you need to multiply 1/5 times 3 because 1/5 mixes with just 1/3 of a cup of nuts...